TINJAUAN PELAKSANAAN PENYIDIKAN TINDAK PIDANA DI KEPOLISIAN PERAIRAN DAERAH SAMARINDA - Pirasman, Ilham Hasri (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTAt present sea transportation in Indonesia is only dominated by freight transportation. The 80 percent of sea transportation that dominates is coal transportation, palm oil transportation, gas transportation, and container transportation. While the traditional passenger and shipping transportation conditions are increasingly abandoned because it is not a priority government policy.The investigation of shipping crime in Samarinda Regional Water Police has been in accordance with what is stipulated in the applicable laws and regulations, although there are still some actions carried out by investigators conducted by investigators not yet regulated in the laws and regulations.The need for an increase in the number of investigators to carry out investigations into shipping crime, especially civil servant investigators (PPNS) at the Samarinda Port Authority Office (KSOP).keywords: investigation, waters police